ANALISIS PENGARUH OPERATING CASH FLOW, PROFITABILITAS, SALES GROWTH, FIRM SIZE, DAN LEVERAGE TERHADAP PREDIKSI KONDISI FINANCIAL DISTRESS - Sholikha, Nikmatus; Febrianti, Devi; Megasyara, Ira; Imawan, Amrizal (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
The phenomenon of PKPU (Application for Insolvency and Delayed Debt Payment) on some issuers in the IDX appears to indicate financial problems (financial distress). The research was conducted to test and analyze the impact of operating cash flow, profitability, sales growth, firm size, and leverage on the prediction of financial distress conditions in sub-sector companies heavy construction and civil engineering registered in the IDX in 2020-2022. The sampling techniques used are purposive samplings with samples obtained of 60 data. The quantitative method is used in this study through an associative approach using secondary data as well as using double linear analysis with the SPSS version 22 test tool. The results of this study show that the profitability variables with proxy return on asset have a significant impact on financial distress, while the operating cash flow, sales growth, firm size, and leverage variables of proxy debt to asset ratio have no influence on financial stress. The implications of this study are expected to inform investors to always do financial analysis first before making decisions in the heavy construction and civil engineering subsectors.